Non-Cell Autonomous Effects of the Senescence-Associated Secretory Phenotype in Cancer Therapy - Saleh, Tareq; Tyutynuk-Massey, Liliya; Cudjoe, Emmanuel K.; Idowu, Michael O.; Landry, Joseph W.; Gewirtz, David A. (Frontiers in Oncology, 2018)
In addition to promoting various forms of cell death, most conventional antitumor therapies also promote senescence. There is now extensive evidence that therapy-induced senescence (TIS) might be transient, raising the concern that TIS could represent an undesirable outcome of therapy by providing a mechanism for tumor dormancy and eventual disease recurrence. The senescence-associated secretory phenotype (SASP) is a hallmark of TIS and may contribute to aberrant effects of cancer therapy. Here, we propose that the SASP may also serve as a major driver of escape from senescence and the re-emergence of proliferating tumor cells, wherein factors secreted from the senescent cells contribute to the restoration of tumor growth in a non-cell autonomous fashion. Accordingly, anti-SASP therapies might serve to mitigate the deleterious outcomes of TIS. In addition to providing an overview of the putative actions of the SASP, we discuss recent efforts to identify and eliminate senescent tumor cells.